Introduction and establishment of fluoroquinolone-resistant Shigella sonnei into Bhutan. Issue 6 (24th December 2015) - Chung The, Hao; Rabaa, Maia A.; Thanh, Duy Pham; Ruekit, Sirigade; Wangchuk, Sonam; Dorji, Tshering; Tshering, Kinzang Pem; Nguyen, To Nguyen Thi; Vinh, Phat Voong; Thanh, Tuyen Ha; Minh, Chau Nguyen Ngoc; Turner, Paul; et al.
Abstract : Shigella sonnei is a major contributor to the global burden of diarrhoeal disease, generally associated with dysenteric diarrhoea in developed countries but also emerging in developing countries. The reason for the recent success of S. sonnei is unknown, but is likely catalysed by its ability to acquire resistance against multiple antimicrobials. Between 2011 and 2013, S. sonnei exhibiting resistance to fluoroquinolones, the first-line treatment recommended for shigellosis, emerged in Bhutan. Aiming to reconstruct the introduction and establishment of fluoroquinolone-resistant S. sonnei populations in Bhutan, we performed whole-genome sequencing on 71 S. sonnei samples isolated in Bhutan between 2011 and 2013.We found that these strains represented an expansion of a clade within the previously described lineage III, found specifically in Central Asia. Temporal phylogenetic reconstruction demonstrated that all of the sequenced Bhutanese S. sonnei diverged from a single ancestor that was introduced into Bhutan around 2006. Our data additionally predicted that fluoroquinolone resistance, conferred by mutations in gyrA and parC, arose prior to the introduction of the founder strain into Bhutan. Once established in Bhutan, these S. sonnei had access to a broad gene pool, as indicated by the acquisition of extended-spectrum β-lactamase-encoding plasmids and genes encoding type IV pili. The data presented here outline a model for the introduction and maintenance of fluoroquinolone-resistant S. sonnei in a new setting. Given the current circulation of fluoroquinolone-resistant S. sonnei in Asia, we speculate that this pattern of introduction is being recapitulated across the region and beyond.